Pengaruh Brand Ambassador, Content Marketing, dan Word Of Mouth Terhadap Keputusan Pembelian Produk Hijab Merek Zoya (Studi Pada Pelanggan Azzam Collection di Kota Jakarta Timur) - Rani Handayani; Hari Susanta Nugraha; Widayanto Widayanto (Universitas Diponegoro, 2024)
Abstract: Zoya is a hijab fashion brand that is quite well known for offering its products to Muslim women in Indonesia. Azzam Collection is one of the shops that sells Zoya hijab fashion in the East Jakarta Administrative City, however, based on Top Brand Index data for the Hijab Category as well as target & sales realization data for Zoya hijab products, there has been fluctuating growth. Brand Ambassador, Content Marketing, and Word of Mouth are thought to be factors that influence purchasing decisions. This research aims to determine the influence of Brand Ambassador, Content Marketing, and Word of Mouth on purchasing decisions for Zoya brand hijab products among Azzam Collection customers in East Jakarta City. The type of research used was explanatory research with a total of 97 respondents. Data processing in this research uses the SPSS Statistics Ver 27 for Macbook tool. The results of this research show that Brand Ambassador, Content Marketing, and Word of Mouth have a positive and significant influence on purchasing decisions for Zoya brand hijab products among Azzam Collection customers in East Jakarta City. The suggestions in this research are that Zoya needs to prepare a PIC (Person in Charge) for Brand Ambassadors, use Google trends/analytics, and maintain and improve the quality and number of product variants.Keywords: purchase decision; brand ambassador; content marketing;word of mouthAbstraksi: Zoya merupakan salah satu merek fashion hijab yang cukup terkenal dalam menawarkan produknya bagi para muslimah di Indonesia. Azzam Collection merupakan salah satu toko yang menjual fashion hijab Zoya di Kota Administrasi Jakarta Timur, namun berdasarkan data Top Brand Index Kategori Hijab serta data target & realisasi penjualan produk hijab Zoya mengalami pertumbuhan yang fluktuatif. Brand Ambassador, Content Marketing, dan Word of Mouth diduga sebagai faktor yang mempengaruhi keputusan pembelian. Penelitian ini bertujuan untuk mengetahui pengaruh Brand Ambassador, Content Marketing, dan Word of Mouth terhadap keputusan pembelian produk hijab merek Zoya pada pelanggan Azzam Collection di Kota Jakarta Timur. Tipe penelitian yang digunakan yaitu explanatory research dengan jumlah responden sebanyak 97 orang. Pengolahan data dalam penelitian ini menggunakan alat bantu SPSS Statistics Ver 27 for Macbook. Hasil penelitian ini menunjukan bahwa Brand Ambassador, Content Marketing, dan Word of Mouth berpengaruh positif dan signifikan terhadap Keputusan Pembelian produk hijab merek Zoya pada pelanggan Azzam Collection di Kota Jakarta Timur. Saran dalam penelitian ini adalah Zoya perlu menyiapkan PIC (Person In Charge) bagi Brand Ambassador, penggunaan google trend/analytic, serta menjaga dan meningkatan kualitas serta jumlah dari varians produknya.Kata Kunci: keputusan pembelian; brand ambassador; content marketing; word of mouth